2009
DOI: 10.1007/s12011-009-8485-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Trace Elements Contents in Asparagus racemosus (Willd)

Abstract: The present study was carried out to determine the accumulation and variation of trace elements in roots and leaves of Asparagus racemosus collected from four different altitudes in Uttarakhand, India, by atomic absorption spectroscopy. The metals investigated were Zn, Cu, Mn, Fe, Co, Na, K, Ca, and Li. The concentration level of Fe was found to be highest at an altitude of 2,250 m, whereas the level of Cu was lowest. The maximum concentrations of Zn, Cu, Mn, Fe, Co, Na, K, Ca, and Li were found to be 165.0 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Asparagus also contains 52.9% carbohydrates which are the main carbon source for bacterial exopolysaccharide production [37]. This extra carbon source improved curdlan production by supplementing the amount of sucrose in MJDA media since sucrose concentration is crucial for curdlan synthesis by Agrobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Asparagus also contains 52.9% carbohydrates which are the main carbon source for bacterial exopolysaccharide production [37]. This extra carbon source improved curdlan production by supplementing the amount of sucrose in MJDA media since sucrose concentration is crucial for curdlan synthesis by Agrobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of vitamins A, C, B 1 , B 2 and E, and folic acid can be found in various AR. Other phytochemical constituents in asparagus are arginine, tyrosine, asparagine, flavonoids (kaempferol, quercetin and rutin), essential oils, resin and tannins (Negi et al ., ). For example, A. adscendens Roxb roots are rich in vitamin C (Prasad et al ., ), an antioxidant compound that protects the human body against free radicals, strengthens the immune system and keeps human gums healthy (Balasubramani et al ., ).…”
Section: Phytochemistry Of Armentioning
confidence: 97%
“…Negi et al reported that A. curillus (Buch.-Ham.) ex-Roxb roots exhibited the highest concentrations of Zn, Cu, Na, K, Ca, and Li, but Mn, Fe, and Co were the highest in A. curillus leaves ( 84 ). Meanwhile, the concentrations of Cu and Mn were low, Zn, Co, Na, and lithium (Li) concentrations were moderate, and K, Ca, and Fe concentrations were very high in A. curillus roots collected from four different altitudes in three seasons.…”
Section: Bioactive Compounds In Asparagusmentioning
confidence: 99%